Implementasi Peraturan Bupati Tegal Nomor 6 Tahun 2019 Tentang Fasilitasi Penumbuhan dan Pengembangan Kewirausahaan di Kabupaten Tegal - Moh Taufik; Bha'iq Roza Rakhmatullah (Kosmik Hukum, 2022)
The Tegal Regency Government under the leadership of Mrs. Umi Azizah created a program to be able to help overcome unemployment, especially among youth in Tegal Regency, by issuing a policy in the form of Regent Regulation Number 6 of 2019 concerning Facilitation of Entrepreneurship Growth and Development for Youth in Tegal Regency. This research is normative juridical research on issues relating to laws and other accompanying regulations regarding youth and entrepreneurship, this study aims to determine the implementation of the Tegal regent's regulation number 6 of 2019 concerning the facilitation of the growth and development of entrepreneurship. in this study using qualitative data analysis methods, namely normative juridical presented descriptively. Regent Regulation number 6 of 2019 made the main strategy, namely the commitment of Tegal Regency to improve the ranking of all indicators in youth and entrepreneurial policies in a better direction, structural improvements for all indicators, increasing independent entrepreneurs who can contribute to the community and the Tegal Regency Regional Government.Keywords: Implementation, Entrepreneurship, Economy of Tegal Regency.